The Role of Web-Sphere for Managing Supply Chain Business Objects in Heterogeneous Systems - Maria Abuzjarova; Chen Yanting; Oleksandr Pidchosa (International Journal of Supply Chain Management, 2020)
Abstract— The study discusses the problem of managing supply chain business objects in heterogeneous systems through the use of Business Process Management Systems (BPMS). The purpose of the research is to summarize the experience of domestic enterprises (operating in logistics and other businesses) when using cloud-based logistics systems; to identify general development trends in the domestic market and to develop recommendations for improving the efficiency of supply chain management based on cloud technologies. The research hypothesis is that the competitiveness of the logistics system grows along with its synergy. To test the hypothesis, a survey of 94 respondents working with such systems has been conducted. It has been found that IBM WebSphere is the most preferable system as it provides the maximum synergistic effect that is achieved by the targeted, coordinated, and mutual operation of two or more digital technologies to achieve a certain common goal. In particular, this stems from the fact that it is not enough to produce quality and essential goods or to provide a service; it is important to be able to convey the message to the consumer. The concept of competition has expanded beyond the boundaries of products (goods or services) and has moved into the sphere of competition among management structures.